The abilities and the use of AutoCAD and its place in the educational process - RÓŻOWICZ, MARIUSZ; MOLGA, AGNIESZKA (Journal of Education, Technology and Computer Science, 2016)
AutoCAD system is commonly available software which forms the basis for computer aideddesign and is a significant work tool for engineers, designers or constructors. This article attemptsto present the system of computer-aided design.